The ideal-actual gap in the roles of research in teaching - Bryan Mallillin Nozaleda; Jhoanna Battung Calubaquib (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aimed to create an image of how research integrates in university teaching particularly in STEM education in a state university in Philippines. The participants were 104 teachers from five campuses of the university that offers STEM undergraduate programs. A quantitative research design was employed to address the central theme: The identification of the gap between the beliefs and perceptions of STEM Educators regarding the role of research in university teaching. T-test was used to test the difference between the actual and ideal beliefs of teachers. Cohen’s d values were computed to determine the effect sizes. The present study revealed that the STEM teachers highly valued the role of research in teaching. They especially considered the development of creative and critical dispositions as the most important goals of integrating research into teaching. However, the teachers reported low actual integration of research into their current teaching, revealing a major gap between their beliefs and the perceived actual integration research into their own teaching practices as evident in the result of the statistical tests. It further showed that institutional background appeared to be critical in the integration of research in teaching. Ultimately, STEM education in the university is emphatic on research content in the delivery of instruction while creating opportunities for learners to participate along the learning process. However, a research-based approach remains to be unpopular, much less for a research-oriented classroom. Strengthening research support and widening the scope of research culture are recommended.